A semi-qualitative approach to the operationalization of the Food–Environment–Energy–Water (FE2W) Nexus concept for infrastructure planning: A case study of the Niger Basin - Seidou, Ousmane; Ringler, Claudia; Kalcic, Spela; Ferrini, Luca; Ramani, Traoré Abdou; Guero, Abdou (Taylor and Francis, 2021)
The countries sharing the Niger River suffer from poor access to clean water and energy as well as food insecurity. The Niger River Basin Authority is tasked with advancing progress in all these areas while also reducing environmental degradation. To help the basin authority and its investors prioritize portfolio activities that support multiple securities of interest, we developed a mixed-methods approach that engaged basin countries in qualitatively ranking projects to meet energy, environmental and food security goals, complemented by quantitative modelling for the more complex ranking of water and environmental sustainability goals, necessitated by complex upstream–downstream linkages.